Zeolites synthesis from phyllosilicates and their performance for CO2 adsorption - Es Sih, Salima; Vilarrasa García, Enrique; De Azevedo, Diana Cristina Silva; Ballesteros-Plata, Daniel; Barroso-Martín, Isabel; Infantes-Molina, Antonia; Rodríguez-Castellón, Enrique; Franco-Duro, Francisco Ignacio; Cecilia-Buenestado, Juan Antonio (Springer, 2024)
Five phyllosilicates (kaolinite, montmorillonite, saponite, sepiolite and palygorskite) have been selected as starting materi- als for the synthesis of zeolites. Among them, kaolinite and montmorillonite display the lowest Si/Al molar ratio leading to aluminosilicates with high crystallinity. Thus, the hydrothermal treatment under basic conditions forms 4A zeolite when kaolinite is used as starting material while 13X zeolite is obtained when montmorillonite is used as starting material. The microporosity and CO 2 -adsorption capacity of the prepared zeolites are directly related to its crystallinity. Thus, in order to improve it, raw phyllosilicates were subjected to a microwave-assisted treatment to remove undesired Mg or Fe-species, which have a negative effect in the assembling of the zeolites by hydrothermal basic conditions in a second step. The high- est adsorption value was 3.85 mmol/g at 25 °C and 760 mm of Hg for Mont-A-B sample after the consecutive treatments.
Keywords: Zeolitas; Filosilicatos; Dióxido de carbono - Absorción y adsorción; Phyllosilicates; Kaolinite; Montmorillonite; 3X zeolite; 4A zeolite; CO2 adsorption